Analisis Kinerja Keuangan dan Pengaruhnya Terhadap Nilai Perusahaan Pada Sektor Infrastuktur Utilitas dan Transportasi di Bursa Efek Indonesia - Hendro, Andi (Movere Journal, 2019)
This study aimed to examine the effect of Debt to Equity Ratio (DER), Earning Per Share (EPS) and Net Profit Margin (NPM) on firm value (Tobins q), simultaneously or partially. Technical research methods associative with linear analysis. The analytical method used is the classical assumption, hypothesis testing and linear regression.The results of this study indicate that simultaneous debt to equity ratio, earnings per share and net profit margin have a significant effect on firm value. Net Profit Margin and Debt to Equity Ratio has a partially significant effect on the value of the company and gives a considerable contribution to the value of the company in the infrastructure utilities and transportation sector on the IDX, the management of infrastructure utility and transportation companies should pay attention to the net profit margin and debt to equity ratio values ​​that will affect the firm value , while Earning per Share do not affect the company's value in the utilities and transportation infrastructure sector on the IDX. Keywords: financial performance, the value of the company